Nursing diagnoses based on the self-care theory in people with visual deficiency - Ellen Lucy Vale de Souza; Gisele Nogueira de Moura; Jennara Candido do Nascimento; Maria Alzete de Lima; Lorita Marlena Freitag Pagliuca; Joselany Áfio Caetano (Universidade Federal do Ceará, 2012)
The study aimed at describing the nursing diagnoses based on the identification of self-care deficit in visually impaired people, using Orem's self-care deficit Theory as framework. This case study was developed with four people with visual impairment, using semi-structured interview and based on the Self-Care Deficit Theory, with identification of nursing diagnoses according to NANDA-I Taxonomy. The following nursing diagnoses were identified: impaired social interaction, self-care deficit, ineffective therapeutic regimen management, risk of changing stress syndrome, sexual dysfunction and impaired physical mobility. It is concluded that the group presented a considerable degree of limitation in the ability to perform self-care. It is noted, however, that the group has the potential to develop skills needed for safe performance of their daily activities, which represents a fruitful field for nursing actions.